Midwifery Philosophy in Islam and Its Implications for Midwifery Practice: A Scoping Review - Nurajizah Kalla; Ismarwati Ismarwati; M. Nurdin Zuhdi (Journal La Medihealtico, 2025)
Modern midwifery practice is increasingly shaped by medical technology and evidence-based approaches, which may at times create ethical and cultural tensions when applied in Muslim contexts. Islamic midwifery philosophy offers a value-based framework that integrates spiritual, moral, and ethical principles with clinical care. This study aimed to explore how the philosophy of midwifery in Islam provides guidance and solutions to challenges encountered in contemporary midwifery practice. A scoping review design was employed following the PRISMA-ScR guidelines. Literature searches were conducted across multiple electronic databases, including PubMed, Google Scholar, Scopus, JSTOR, ScienceDirect, and university libraries. Studies published between 2019 and 2025 that addressed Islamic values, ethics, or philosophy in relation to modern midwifery practice were included. Of 1,013 records identified, six studies met the final inclusion criteria and were analyzed thematically. The findings indicate that Islamic midwifery philosophy supports woman-centered, culturally sensitive, and holistic care, emphasizing respect for dignity, informed decision-making, ethical use of medical technology, and attention to emotional and spiritual well-being. Islamic values were found to enhance communication, trust, and patient engagement without opposing evidence-based practice. This review concludes that Islamic midwifery philosophy complements modern midwifery by providing ethical and practical guidance that strengthens culturally responsive, safe, and patient-centered maternity care in contemporary healthcare settings